Entrepreneurial Networking and Women Entrepreneurs’ Contribution to Employment Creation in Rivers State, Nigeria - Victor, ADIM Chidiebere; M.B.O, ADELAIYE; Ernest, ADUBASIM Ikechukwu (International Journal of Business, Economics and Management, 2018)
The purpose of this study was to examine the relationship between entrepreneurial networking and women entrepreneurs’ contribution to employment creation in Rivers State, Nigeria. The study adopted a cross sectional survey design to solicit responses from women entrepreneurs in Rivers state, using simple random. The target population of Women Entrepreneurs in Rivers State was 329 obtained from the 2017 Directory of the Rivers State Ministry of Women Affairs and Rivers State Ministry of Commerce and Industry. The sample size was 181 using the Taro Yamen’s formula. After data cleaning, only data of 153 respondents were finally used for data analysis. Descriptive statistics and Spearman’s rank correlation were used for data analysis and hypothesis testing. Findings revealed that entrepreneurial networking has a significant relationship with women entrepreneurs to employment .The study thus concluded that entrepreneurial networking bears a positive and significant influence on women entrepreneurs’ contribution to employment creation. We recommend that women should be engaged in entrepreneurial education to develop right competencies, skills and needed entrepreneurial capacities.